Gender Equality In Islam: Concepts, Principles, and the Role of Women in Da’wah - Meiviani Nurul Aisyah Maulana; Hikma Nurfadila; Taufiqurrahman; Mutiara Ariska; Erni Haryanti (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2025)
This study explores gender equality in Islam through three main dimensions: the fundamental concepts of gender and equality, the Islamic principles of justice, and the strategic roles of women in da’wah and education. Employing a qualitative descriptive method with a library research approach, this research draws on primary sources (the Qur’an and Hadith) and contemporary academic literature. Data were analyzed thematically through stages of reduction, presentation, and conclusion. The results indicate that Islam provides strong theological and social foundations for promoting equitable and contextual gender equality. Conceptually, gender is viewed as a social construct that can be reconstructed through critical awareness and justice-oriented interpretation. The principles of monotheism and justice in Islam affirm the spiritual and social equality of men and women while acknowledging their natural distinctions. In da’wah and education, women serve as educators, agents of social transformation, and active contributors in both domestic and public spheres. The study concludes that gender equality in Islam is not an adaptation of modern values but an intrinsic expression of divine justice and human dignity contained within Islamic revelation.